Challenges and Coping Strategies in Licensure Examination Among Electrical Engineering Graduates - Ampuan, Bless G. (Journal of Engineering Education Transformations, 2025)
This quantitative study employed a descriptive survey design utilizing a stratified sampling technique. Slovin’s formula was applied to determine the sample size from each batch, resulting in a total sample size of 70. Findings revealed that distraction and creating a relaxed study environment is the most prevalent challenges and coping strategies, respectively. Major challenges were encountered such as the numerous formulas to memorize, financial issues and societal expectations which contributed to the difficulties of the graduates in their preparation. Major coping strategies such as early preparation, practice by solving more problems, understanding the formula, preparing a study plan, and the use of review materials gathered from the review center are the major contributors to the successful electrical engineering students, implicating a significant factor in passing the licensure examination. This study aimed to enhance the productivity of graduates in licensure exams and contribute to higher passing rates.